Visual anatomy & physiology - Frederic H. Martini (Pearson, 2015)
Visual Anatomy & Physiology combines a visual approach with a modular organization to deliver an easy-to-use and time-efficient book that uniquely meets the needs of today's students-without sacrificing the comprehensive coverage of A&P topics required for careers in nursing and other allied health professions. The Second Edition addresses tough physiology topics with new and revised two-page modules. Brand-new end-of-chapter study and practice materials include a narrative Study Outline and comprehensive Chapter Review Questions. Module Reviews and Section Reviews, appearing throughout each chapter, give students additional tools for learning